Hydrostannolysis reactions-II. Reaction of phenolic esters with tri-n-butyltin hydride - Khoo, L.E.; Lee, H.H. (Elsevier, 1970)
Reaction of phenyl benzoate with tri-n-butyltin hydride has been found to give mainly toluene, benzyl benzoate, tri-n-butyltin phenoxide and tri-n-butyltin benzoate. Possible reaction paths leading to these products are discussed. A SH2 mechanism involving initial attack of tri-n-butyltin radical at the ethereal oxygen atom of the ester with displacement of the benzoyl moiety appears to be consistent with observed experimental evidence. © 1970.